Imagination, ecologized and enacted: driven by the historicity of affordance competition - Stankozi, Caroline (Frontiers in Psychology, 2024)
Together, ecological psychology and enactivism can explain imagination as being driven by affordance competition. This paper presents synaptic plasticity as a hotspot for the respective historicity. First, (i) affordances are introduced as directly perceptible on the ecological view, and as co-created by an individual on the enactive view. After pointing out their compatibility, (ii) empirical underpinnings of the historicity of affordance competition are summarized and followed by a nonrepresentational interpretation thereof. They are used to explain: (iii) What affords imagining? After discussing both van Dijk and Rietveld's (2020) non-representational answer and McClelland's (2020) representational one, I propose a more general explanation: a stand-off between competing affordances can be resolved by imagination, driven by affordance competition. Arguably, (iv) the sensorimotor traces of previous interactions (e.g., strengthened synapses) can be repurposed as representations -grounding even representational explanations in an ecologized enactive framework.